ADVANCING DIVERSITY RESEARCH THROUGH COGNITIVE ANALYTICS: DEVELOPMENT AND VALIDATION OF A COGNITIVE AUTONOMY ASSESSMENT DEVICE - S. KUMARAN ARUL DEVARAM; Dr.S.GUNASEKARAN (The Bioscan, 2026)
The increasing emphasis on diversity, equity, and inclusion in contemporary education has created a need for innovative assessment tools capable of capturing learners’ cognitive independence across diverse cultural, linguistic, and educational backgrounds. This study presents the development and validation of a Cognitive Autonomy Assessment Device (CAAD), an innovative cognitive analytics instrument designed to evaluate learners’ capacity for independent thinking, decision-making, problem- solving, self-regulation, and reflective judgment. The device integrates cognitive analytics techniques with psychometric assessment principles to generate comprehensive measures of cognitive autonomy among heterogeneous learner populations. A mixed-method research design was employed, involving instrument construction, expert validation, pilot testing, and large-scale field implementation among undergraduate students representing diverse demographic groups. Statistical analyses, including reliability testing, exploratory factor analysis, and construct validation procedures, confirmed the robustness and consistency of the instrument. The findings indicate that the CAAD effectively identifies variations in cognitive autonomy levels across diverse learner categories while maintaining high validity and reliability standards. Furthermore, the study demonstrates how cognitive analytics can contribute to diversity research by providing evidence-based insights into learners’ cognitive development and educational needs. The proposed assessment framework offers significant implications for educational policy, curriculum design, learner support systems, and inclusive pedagogical practices. The study contributes to the growing body of diversity research by establishing a scientifically validated tool for measuring cognitive autonomy in increasingly diverse educational environments.